Benthic mucilage blooms threaten coralligenous reefs. (September 2018) - Piazzi, L.; Atzori, F.; Cadoni, N.; Cinti, M.F.; Frau, F.; Ceccherelli, G.
Abstract: Mucilaginous aggregates produced by planktonic or benthic algae are considered ecological threats to marine systems. The study evaluated the effects of the spread of benthic mucilaginous aggregates on the structure of coralligenous assemblages. The assemblage and the quality of a site subjected to a benthic mucilage bloom were compared to those of two reference sites using a Before/After-Control/Impact (BACI) design. Results showed the α and β-diversity, ESCA and COARSE quality ecological indices and the cover of encrusting algae and bryozoans were lower at the impact site after the mucilage event than at the control sites and at the impact site before the mucilage event. An opposite pattern was observed for the necrosis of gorgonians and the cover of algal turf. This study describes for the first time the impacts of ephemeral mucilage blooms on the whole coralligenous assemblage, identifying a further threat of this habitat and the need of adequate monitoring programs. Highlights: Benthic mucilaginous aggregates are ecological threats for marine systems. Effects of mucilaginous aggregates on coralligenous reefs are investigated. A Before/After-Control/Impact (BACI) design was used to assess the impact. Biodiversity and abundance of sensitive taxa decreased in impacted site. ESCA and COARSE ecological quality indices decreased in impacted site.